Analisis Putusan Pengadilan Agama Nomor 2429/Pdt.G/2023/PA.Mdn Tentang Nafkah Iddah dan Mut’ah oleh Suami Kepada Isteri dalam Perkara Cerai Talak - Alya, Aulia; Zainuddin, Zainuddin (UNES Law Review, 2024)
The husband is required to give his wife nafkah iddah and mut'ah in a talak divorce; nafkah iddah is an allowance paid during the iddah period, and mut'ah is an allowance for the divorce term. The national laws that are in effect in the country govern efforts to settle court rulings. Settlements are typically reached through the family court system or the mediation process. The Religious Court Number 2429/Pdt.G/2023/PA.Mdn decided that although the panel of judges had required the applicant and respondent to use mediation, their attempts to reach an amicable agreement through mediation had failed. Subsequently, the case analysis proceeded by presenting the contents of the letter sent by the petitioner, which she kept on file. The spouses may pursue a just settlement in compliance with the relevant legal framework.